2013
DOI: 10.1016/j.ijmedinf.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Using informatics to capture older adults’ wellness

Abstract: Purpose The aim of this paper is to demonstrate how informatics applications can support the assessment and visualization of older adults’ wellness. A theoretical framework is presented that informs the design of a technology enhanced screening platform for wellness. We highlight an ongoing pilot demonstration in an assisted living facility where a community room has been converted into a living laboratory for the use of diverse technologies (including a telehealth component to capture vital signs and customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 56 publications
(44 reference statements)
0
61
0
2
Order By: Relevance
“…We created hand sketches of several ideas for each concept and conducted an evaluation session with researchers in gerontological care. Based on our initial sketches, the researchers' feedback, and preferences expressed by community-dwelling older adults in earlier sessions, 18,19 we created four design goals for guiding our preliminary data visualization wireframes:…”
Section: Design Of Health Visualizationsmentioning
confidence: 99%
“…We created hand sketches of several ideas for each concept and conducted an evaluation session with researchers in gerontological care. Based on our initial sketches, the researchers' feedback, and preferences expressed by community-dwelling older adults in earlier sessions, 18,19 we created four design goals for guiding our preliminary data visualization wireframes:…”
Section: Design Of Health Visualizationsmentioning
confidence: 99%
“…In the course of the study 7 participants discontinued participation before completion. Reasons for attrition varied and included death of spouse (1), illness/ hospitalization (2), and other time commitments (3). The issue of attrition due to illness/hospitalization introduces the problem of missing data not at random which must be carefully addressed in future studies to avoid bias.…”
Section: Attritionmentioning
confidence: 99%
“…1 Hoyman further explored the multidimensional nature of wellness by emphasizing that the person needs to be examined in their everyday milieu and suggested that four dimensions are addressed: (1) physical well-being/ fitness; (2) mental and cognitive health; (3) social well-being; and (4) spiritual well-being. 2 (For full discussion, please see Demiris et al 3 )…”
Section: Introductionmentioning
confidence: 99%
“…In such case, constructive integration of information and communication technologies (ICT) like Telehealth to public health informatics (PHI) is seen as an effective and favorable solution to the most pressing healthcare issues and demands of health promotion among the elderly. Telehealth systems hold the premise of helping older adults to live an independent life (Pountney, 2009;Milligan, Roberts, & Mort, 2011); empower patients; and promote selfmanagement (Suter, Suter, & Johnston, 2011) across geographical distance (Demiris et al, 2013;Sorrells-Jones, Tschirch, & Liong, 2006). Moreover, the increasing healthcare cost associated with aging creates diverse market opportunities for Telehealth (DelliFraine, & Dansky, 2008).…”
mentioning
confidence: 99%